MENINGKATKAN PARIWISATA BALI MELALUI KEPASTIAN PENEGAKAN HUKUM ATAS PELANGGARAN KAWASAN TANPA ROKOK DALAM PERATURAN DAERAH PROPINSI BALI NOMOR 10 TAHUN 2011 - I Gusti Agung Ngurah Iriandhika Prabhata (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
To obtain a good and healthy environment is a part of human rights, as stated in the constitution of the Republic of Indonesia and the global principles of human rights. Tourism in Indonesia held on the principle of upholding human rights, especially Bali which engaged in the tourism sector. In response to the Bali Provincial Government policies governing the protection of human rights to obtain a good and healthy environment, through the Bali Local Regulation No. 10 Year 2011 on No Smoking Area, but the policy can not work effectively due to the lack of certainty in terms of law enforcement that is set in the substance of the local regulation (vagueness of legal norms), as well as penalties for violations that have not been able to provide a deterrent effect. This research uses normative legal research with the rationality that this study will examine the substance of the local regulation of Bali Province perceived No Smoking Area considered as vagueness of legal norm. The approach used to solve the problem is through the statute approach, analitical legal and conceptual approach, as well as the comparative approach to do a comparison of the rules banning smoking in Singapore and Queensland Australia. The results showed that a good alternative No Smoking Area policy in Bali is reforming the Bali Local Regulation by inserting a clear formulation of the law enforcement authorities, as well as the formulation of assertive sanctions to provide a deterrent effect. Through law enforcement certainty No Smoking Area, it will be able to improve the quality of tourism in Bali, especially in terms of Cleanliness Personality and Comfort.